Análises bacteriológicas de vibrios e exame presuntivo no camarão (litopenaeus vannamei) cultivado em sistema semiintensivo de baixa salinidade - Lopes, Beatriz Cristina (2020)
The research aimed to relate the bacteriological analyzes of vibrio with the presumptive indicative analysis of vibriosis in the marine shrimp Litopenaeus vannamei grown in a low-salinity semi-intensive system submitted to two production cycles in order to improve the results in the shrimp farms.The study was developed in the field, using three nurseries called V11, V12 and V13 in two production cycles in a semi-intensive system with low salinity. With weekly collections, the experiment started in April 2019, extending until October 2019. The correlation between the positive sucrose and negative sucrose vibrios count with the variables of the presumptive analysis (Hepatopancreas Tubules-P1, Necrosis in hepatopancreas -P2, calcium deposition -P3, color of uropodsP4 and black spot -P5) and with salinity, temperature, pH and dissolved oxygen (O2) in the water. In cycle I, the negative sucrose bacteria showed a positive correlation with water temperature, with P2 and with P5. And also a negative correlation between negative sucrose and P3.In the second cycle, there was a positive correlation between negative sucrose with water pH, P2 and P5 and a negative correlation between negative sucrose with O2 and P4. In all the nurseries and cycles, the positive sucrose bacteria V. Cholera and V. alginolyticus, and the negative sucrose bacteria were identified V. parahaemolyticus and V. Vulnificus. It was realized that contamination of shrimp close to 104 UFC/g associated with the presence of necrosis in the hepatopancreas and black spot can confirm an indication of vibriosis. It is concluded that the presumptive analysis with high indices of necrosis characteristics in the hepatopancreas and black spot may suspect vibriosis, being confirmed by the traditional microbiological technique. This will allow breeders to take care of handling more quickly from the presumptive examination in the field